Hijacking tRNAs From Translation: Regulatory Functions of tRNAs in Mammalian Cell Physiology - Avcilar-Kucukgoze, Irem; Kashina, Anna (Frontiers in Molecular Biosciences, 2020)
Transfer tRNAs (tRNA) are small non-coding RNAs that are highly conserved in all kingdoms of life. Originally discovered as the molecules that deliver amino acids to the growing polypeptide chain during protein synthesis, tRNAs have been believed for a long time to play exclusive role in translation. However, recent studies have identified key roles for tRNAs and tRNA-derived small RNAs in multiple other processes, including regulation of transcription and translation, post-translational modifications, stress response, and disease. These emerging roles suggest that tRNAs may be central players in the complex machinery of biological regulatory pathways. Here we overview these non-canonical roles of tRNA in normal physiology and disease, focusing largely on eukaryotic and mammalian systems.